Earthquake early warning system using ADXL335 accelerometersensor based on IoT - Faisal Lubis; Bakti Viyata Sundawa; Cholish Cholish; Abdullah Abdullah (Jurnal Mantik, 2023)
Earthquakes are vibrations that occur on the earth's surface due to the sudden release of energy from within the earth that creates seismic waves. Earthquakes are usually caused by movement of the earth's crust (plates). The frequency of an area, refers to the type and size of earthquakes experienced over a period of time. Often with the development of technology, it provides a solution to minimize the impact of earthquake events. For this reason, an earthquake warning alarm is needed as an early warning and anticipation of the community when an earthquake occurs. Therefore, researchers made a tool which uses the Accelerometer sensor and arduino nano as a controller and is accompanied by the blynk application as an earthquake early warning notification sent via smartphone. This tool is processed using an Arduino Nano microcontroller as a controlling component. The working system of this tool uses an 8 Volt lithium battery installed in series as a voltage source, which will be reduced to 5 Volts with a stepdown module, because by using a battery voltage of 8 Volts and coupled with a lot of load, the Arduino Regulator IC will experience overheating or heat up quickly. This tool has been successfully designed with manual testing to be able to see the sensitivity of the earthquake sensor made, by utilizing seismic waves that arise due to ground movement. This tool successfully detects earthquakes with horizontal and vertical vibrations, and this tool is quite effective because it does not detect vibrations generated in the surrounding environment. Based on the tests carried out, at an accelerometer sensor tilt angle of 90o the system reads an earthquake strength of around 7-10 Richter Scale (SR) with a WASPADA status